Rumen Bacteria Communities and Performances of Fattening Lambs with a Lower or Greater Subacute Ruminal Acidosis Risk - Li, Fei; Wang, Zhilan; Dong, Chunxiao; Li, Fadi; Wang, Weimin; Yuan, Zehu; Mo, Futao; Weng, Xiuxiu (Frontiers in Microbiology, 2017)
Several ruminal cellulolytic bacteria species are sensitive to pH and could therefore be used as biomarkers to determine the risk of sub-acute ruminal acidosis (SARA) in finishing lambs. This study compared a 2-4 h post feeding ruminal pH measurement to abundances of the ruminal pH-sensitive bacteria to evaluate the risk of SARA in a herd of 120 finishing lambs. The lambs were reared in individual units for 50 d. Ruminal fluid was collected by use of an orogastric tube on day 51 2-4 h after feeding. Although the lambs were fed an identical diet, they responded differently in the abundances of four ruminal pH sensitive cellulolytic bacteria (R. albus, R. flavefacients and F.succinogenes and B. fibrisolvens). Lambs with the most or the least cellulolytic bacteria were then classified as either lower SARA risk (LSR, n = 10) or higher SARA risk group (HSR, n = 10), respectively. Data showed that the ruminal pH and VFA profiles were uncorrelated with the number of cellulolytic bacteria (P > 0.050). Lambs with the HSR showed lower ruminal pH (P = 0.013) and acetate to propionate ratio (P = 0.018), higher concentrations of lactate (P = 0.035) and proportion of propionate (P = 0.033) compared to those with the LSR. The DMI and ADG did not differ in LSR and HSR lambs (P > 0.050). A diversity analysis revealed significantly lower diversity in HSR lambs than in LSR (Simpson index, P = 0.004). The relative abundances of the phyla Bacteroidetes, Fibrobacteres, Verruomicrobia, and Proteobacteria were higher in LSR lambs than in HSR (P < 0.050). The abundances of several phyla including Firmicutes, Tenericuutes and Actinobacteria were higher in the HSR than in the LSR group (P < 0.050). The bacterial communities of the LSR and HSR clustered separately in rumen based on the Unifrac distances, indicating distinct bacteria communities at OTU level between the LSR and HSR lambs. Overall, there was no correlation between 2-4 h post-feeding ruminal pH and the abundance of pH-sensitive bacteria and the amount of these bacteria could be used as a potential biomarker of SARA in lamb herd.